A Design of Supply Chain Risk Management for Cocoa Based Agroindustry at South Sulawesi to Balance Risk - Aisyah, Siti; Nugroho, Bayu Hari; Tampubolon, Salmon; Jaqin, Choesnul; Sumasto, Fredy (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2023)
Cocoa agroindustry in South Sulawesi experienced problems such as imbalance of supply chain management and profit distribution of risks assumed by each of the actors in the supply chain. Those issues became the driving factors that interfere with the emergence of a variety of risk supply chain sustainability. Appropriate risk management processes required by the model approach to create a balanced risk among supply chain actors. This study aims to design a model to ensure and increase profit cocoa supply chain actors. Risk mitigation approach implemented with the risk sharing model which aims to improve profitability and continuity supply chain’s actor. The orientation of the model output is not only to sustain the supply chain but at the same time to increase the total profit on the whole supply chain actors. Balancing risk optimization are done through risk specific calculation and performance of supply chain actors into risk sharing models. The performance of each supply chain actors is calculated with the DEA approach. Total profit improvement among supply chain actor causing risk sharing models in this study have a good bargaining position against all supply chain actors. The design of the of contract structure resulted a form of quantitative models as a tool for coordinating mechanism of risk sharing models for supply chain actors. Through the risk sharing model approach in this study, the design of the supply chain can be produced that have sustainability as well as profitability.